IWD 2021 – Bethlehem Gelgelo on leading EthioChicken in Ethiopia during the COVID-19 pandemic - International Livestock Research Institute (International Livestock Research Institute, 2021)
Bethlehem Gelgelo shares her experience in leading the EthioChicken company in Ethiopia during the COVID-19 crisis. Visit https://www.ilri.org/iwd2021 for more information.